Early Fault Diagnosis of Gear Box based on Variational Mode Decomposition and Fast Spectral Kurtosis - Zhao Wei (Jixie chuandong)
Aiming at the gear fault early sign signal is weak and the noise influence is serious,it is difficult to extract the fault characteristic frequency and band-pass filter parameters are not easy to determine the problem,a fault diagnosis method is proposed based on the variational modal decomposition（VMD） and fast spectral kurtosis（FSK）. Firstly,the vibration signal of the bearing fault is decomposed by VMD to get a series of band-limited intrinsic mode functions（BLIMFS）. Then,according to the correlation coefficient criterion,the spectral kurtosis is calculated for the components with large correlation coefficient,and the best center frequency and bandwidth are determined by spectral kurtosis graph. Finally,the filtered signal is analyzed by the energy operator envelope demodulation. The fault characteristic frequency can be extracted accurately from the envelope spectrum. Through the analysis of simulation signal and experimental data of gear fault,the results show that the method can effectively reduce the influence of the noise and accurately realize the extraction of weak gear fault feature information.